Mejoramiento de la habilidad de lectura a través de la implementación de materiales auténticos con los estudiantes del 2do año de bachillerato de la unidad educativa “Fernando Suárez Palacio”, durante el año lectivo 2014-2015 - González Carrión, Erika Lucia (2016)
The aim of this research work was to improve reading skills through the implementation of authentic materials among 2nd year students of bachillerato, at “Fernando Suárez Palacio”, during the school year 2014-2015. The scientific, the descriptive, the analytic-synthetic and the statistical methods helped to make the analysis and process the information. Tests and questionnaires were applied to twenty-three students at the beginning and at the end of the intervention plan to determine their reading level in English and their perception of the use of authentic materials in the classroom. The results demonstrated that students increased noticeably their level by relating words with sounds and associating them with pictures, making rhymes, summarizing and inferring information and reading without hesitation. As a conclusion, the application of reading authentic materials contributed to improve the reading level in English and motivated students to read inside and outside the classroom and in real contexts effectively.